ISLAM IDEOLOGIS DAN GERAKAN POLITIK ISLAM KONTEMPORER - Karim, Syahrir (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2016)
Islamic politics always played a key role in the formation of Indonesian national identity, even though Islam was finally compromised in the process of establishing the identity. Islam however was able to give strong influence within Indonesian history. This in turn gives Islam a space to deeply take part in the development of Indonesian politics until now. In another side, the role of political parties, particularly Islamic ones, will always shape the discourse of Islamic party in Indonesia, which in turn will be an indicator for the ongoing involvement of Islamic politics in Indonesia.